Republic of Poland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Selected issues of Poland are studied in this paper. The global projection model used to prepare the baseline inflation forecast and risk assessment for Poland is also explained. Baseline forecast, risk assessment, and policy communication are discussed. The pension reform has been a cornerstone of fiscal policies in Central and Eastern Europe (CEE). Problems with the Stability and Growth Pact (SGP) rules, a brief discussion of reform reversals, and policy options for both individual countries and those at the EU level are also discussed. Fiscal implications of pre-funding future liabilities are also studied.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet